Study on Relationship of Serum Total Cholesterol Low Density Lipoprotein and Triglycerides With Body Mass Index - Hossain, Kamal; Hoque, Mahmudul; Faiz, Saifur Nahar; Alam, ASM Towhidul (Journal of Chittagong Medical College Teachers' Association, 2013)
The present case control study was designed to determined the relationship between serum Total cholesterol, Low Density Lipoprotein (LDL), Triglycerides (TG) and Body Mass Index (BMI). The study was carried out in the Department of Biochemistry Chittagong Medical College during the period of January 2010- December 2010. Samples were collected from population of different area of Chittagong City Corporation of different occupations, age from 35- 60 years. The data were collected by a structured questionaries which includes age, sex, occupation, dietary habits, family history of hyperlipidemia and DM. BMI was calculated by standardized protocol. Population suffering from DM, renal diseases and other endocrine disease were excluded. A total of 105 subjects were included in this study. Among them 70 were considered as case ( whose BMI was 25 kg/m2) and 35 were considered as control ( whose BMI was < 25 Kg/ m2).Serum Total cholesterol, LDL-C, HDL-C and TG were measured in all samples in fasting state. Study showed that female were more obese than male,( 31.14 +2.23kg/m2 Vs 29.71 +2.69kg/mo), p= <0.05.Results showed that Serum TC(45%), LDL-C(65%), TG(70%) were significantly higher in cases than that of controls (p=<0.001).Serum HDL-C(35%) was significantly decreased in cases than that of controls (p=<0.001).Study showed that hypertriglyceridemia (70%) was the common lipid abnormality and then LDL-C (65%). Study revealed that there was no significant difference in lipid profile between male and female. Pearson's Correlation Coefficient showed that there were positive correlation between TC (r=0.234,p=<0.05), LDL-C (r=0.258,p=<0.01), TG (r=0.409,p=<0.001) and BMI, and was negative correlation between HDL-C(r= -0.403, p= <0.001) and BMI. So early detection and prevention of obesity and abnormal lipid profile can largely reduce morbidity and mortality and alleviate undue burden on our limited health budget. JCMCTA 2012 ; 23 (2): 22-26